Keberlanjutan Program Kartu Lanjut Usia Terlantar di Daerah Khusus Ibukota Jakarta - Andito, Ario Seno; Yusuf, Maulana; Rahmawati, Rahmawati (ANTASENA: Governance and Innovation Journal, 2026)
Abstract The Jakarta Elderly Card (Kartu Lansia Jakarta/KLJ) is one of the flagship social assistance programs of the Provincial Government of DKI Jakarta aimed at improving the welfare of neglected elderly people through the fulfillment of their basic needs. The program is regulated under Governor Regulation of DKI Jakarta Number 44 of 2022 and serves as part of the government's social protection efforts for vulnerable groups. Although the program has been implemented continuously, several challenges remain, including discrepancies between targeted and actual beneficiaries, changes in beneficiary application procedures, and reductions in the amount of assistance provided. This study aims to evaluate the sustainability of the KLJ Program in supporting the fulfillment of basic needs among neglected elderly citizens in DKI Jakarta. The study employed a descriptive qualitative approach. Data were collected through observation, in-depth interviews, and documentation. Research informants included local government officials as policy makers, village-level administrators as program mediators, social facilitators, and elderly beneficiaries. The findings indicate that the sustainability of the KLJ Program still faces challenges in the resource dimension, particularly the reduction in assistance funds, which may affect the program’s effectiveness in meeting the basic needs of elderly beneficiaries. However, from the regulatory perspective, the program has established clear standard operating procedures. Furthermore, the Social Affairs Office of DKI Jakarta Province regularly provides technical guidance to social facilitators to improve assistance services and ensure that information regarding social assistance is accurately delivered to beneficiaries.